An Imperfect Firewall: Quebec’s Constitutional Right of Secession as a Device Against Domination - Pérez-Lozano, Lluís (2021)
The idea of including a right of secession in democratic constitutions has been discussed by different political and legal theorists; however, little has been said on the matter from the point of view of democratic-republican political philosophy. This article undertakes this effort by means of a normative analysis of Quebec’s constitutional right of secession, as outlined in the Quebec Secession Reference. This analysis shows how the non-unilateral nature of this right minimises the risks for republican freedom (as non-domination) and inclusion in the Quebec secession conflict, while the fact that it is limited to a national constitutional framework dampens this achievement.